2019
DOI: 10.1007/s11145-019-09962-7
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the serial advantage in the naming rate of multiple over isolated stimulus displays

Abstract: We thank Dimitris Sagris and Iliana Kolotoura for help administering the tasks and processing the responses in Greek, and Megan Boonstra for help administering the tasks and processing the responses in English.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
22
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 54 publications
7
22
2
Order By: Relevance
“…Second, the items must be arranged in an array or grid and named in the left-to-right, row-by-row fashion that is analogous to reading in English. Naming items that are presented one at a time in a speeded manner (discrete naming) is not the same as the serial process of a true RAN task (Altani et al, 2020;de Jong, 2011;Logan et al, 2011;Protopapas et al, 2013), despite the fact that some studies call this "discrete RAN." Third, the RAN measure is usually based on time to complete the task.…”
Section: Defining Ran Tasksmentioning
confidence: 99%
“…Second, the items must be arranged in an array or grid and named in the left-to-right, row-by-row fashion that is analogous to reading in English. Naming items that are presented one at a time in a speeded manner (discrete naming) is not the same as the serial process of a true RAN task (Altani et al, 2020;de Jong, 2011;Logan et al, 2011;Protopapas et al, 2013), despite the fact that some studies call this "discrete RAN." Third, the RAN measure is usually based on time to complete the task.…”
Section: Defining Ran Tasksmentioning
confidence: 99%
“…Likewise, outcomes on the two kinds of measures should be almost identical. However, multiple studies have shown that this is not the case (e.g., de Jong, 2011;Protopapas et al, 2013;Altani et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the word-list reading of familiar words (i.e., short words of high frequency that are likely to be read by sight), multiple studies have shown that individual word recognition speed is only a moderate predictor of serial word reading rate (Protopapas et al, 2013;Altani et al, 2017Altani et al, , 2020. Additionally, several studies have shown that the relation between individual word recognition speed and serial word reading rate decreases over time (Protopapas et al, 2013(Protopapas et al, , 2018Altani et al, 2020). The predictive power of individual word recognition skill is weakened as children become more skilled readers and are able to read word lists more fluently (de Jong, 2011;Altani et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations